COMMUNITY PREPAREDNESS FOR NATURAL DISASTERS IN CIKAHURIPAN VILLAGE, LEMBANG DISTRICT, WEST BANDUNG REGENCY - Larasati, Andini; Aritonang, Admiral Nelson; Hekmatyar, Versanudin (Indonesian Journal of Social Work, 2025)
This study aims to determine the level of disaster preparedness among the community of Cikahuripan Village, Lembang Subdistrict, West Bandung Regency, in facing 4 natural hazards. A quantitative descriptive approach was used, applying the LIPI– UNESCO/ISDR (2006) instrument, which consists of four parameters: disaster risk knowledge, emergency response planning, early warning systems, and resource mobilization. A total of 98 respondents from all neighborhood units (RW) in the village were selected as the research sample. The results showed that the Community Preparedness Index (CPI) reached 74.2, which falls into the "Prepared" category. The highest score was in disaster risk knowledge (83.15), followed by emergency response planning (76.4), early warning systems (67), and the lowest score was in resource mobilization (46.5). The low score in resource mobilization indicates a lack of capacity among residents in organizing logistics, emergency funds, and asset protection during disasters. Based on these findings, a community-based intervention program named "SIAGA CIKAHURIPAN" was designed, focusing on simulation and training activities to enhance the community's ability to mobilize local resources. The program is structured to involve village authorities, community organizations, women, and youth as key actors. This research is expected to serve as a reference for disaster preparedness policy development and the implementation of community-based disaster management programs in high-risk rural areas